2022
DOI: 10.1016/j.radonc.2021.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Current practice in proton therapy delivery in adult cancer patients across Europe

Abstract: Background and purpose: Major differences exist among proton therapy (PT) centres regarding PT delivery in adult cancer patient. To obtain insight into current practice in Europe, we performed a survey among European PT centres. Materials and methods: We designed electronic questionnaires for eight tumour sites, focusing on four main topics: 1) indications and patient selection methods; 2) reimbursement; 3) on-going or planned studies, 4) annual number of patients treated with PT. Results: Of 22 centres, 19 (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…The tumour entities treated by most participating centres are brain and head and neck tumours, which is in line with a study on the current practice in proton therapy delivery in Europe [35]. In brain tumour patients, radiosensitive OAR are usually situated close to the target volume, resulting in areas being exposed to high dose and high LET and, therefore, at risk of more pronounced clinical effects due to an elevated RBE dose.…”
Section: Discussionsupporting
confidence: 55%
“…The tumour entities treated by most participating centres are brain and head and neck tumours, which is in line with a study on the current practice in proton therapy delivery in Europe [35]. In brain tumour patients, radiosensitive OAR are usually situated close to the target volume, resulting in areas being exposed to high dose and high LET and, therefore, at risk of more pronounced clinical effects due to an elevated RBE dose.…”
Section: Discussionsupporting
confidence: 55%
“…Although the number of PT centers increased rapidly, their average volume was relatively stable. According to surveys of European PT centers, in 2020, the average number of patients treated by a PT center is 223 (range of 29–950) ( 25 , 26 ), which is similar to that in 2015 (221, range of 40–557) ( 26 ). Thus, increasing the number of PT centers played an important role in getting more patients treated by PT.…”
Section: Discussionmentioning
confidence: 53%
“…( 25 , 26 ) In this study, we found the extremely high inequality in accessibility of PT centers among all countries in the world (Gini = 0.96), which is even more severe than the inequality observed in economic development (Gini = 0.87 for GDP). Our empirical data analyses showed that the total GDP had a significant impact on whether a country had a practical PT center, whereas the total GDP and GDP per capita had significant impacts on the number of PT centers.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations